Clinical Multi-Omics Study on the Gut Microbiota in Critically Ill Patients After Cardiovascular Surgery Combined With Cardiopulmonary Bypass With or Without Sepsis (MUL-GM-CSCPB Study): A Prospective Study Protocol - Ding, Wenyan; Liu, Jianzhou; Zhou, Xiang; Miao, Qi; Zheng, Haibo; Zhou, Baojin; Dou, Guifang; Tong, Yigang; Long, Yun; Su, Longxiang (Frontiers in Medicine, 2020)
Introduction Fever of unknown origin (FUO) and haemodynamic instability are complications after cardiac surgery combined with cardiopulmonary bypass (CPB) for heart disease. Patients who develop fever with haemodynamic instability after cardiac surgery may have systemic inflammatory response syndrome or sepsis. Cardiopulmonary bypass (CPB) is a technique that temporarily takes over the function of the heart and lungs during cardiac surgery. Recent reports suggest that the early bloodstream infections of patients undergoing CPB are due to gram-negative bacteria that are present in the intestinal flora. The theory of intestinal flora translocation has growing evidence. Intestinal ischaemia-reperfusion that occurs during cardiac surgery with CPB will induce a systemic inflammatory reaction and may cause intestinal flora translocation. Does this systemic reaction cause sepsis? Thus, we propose this protocol to determine whether the changes in the intestinal flora in patients after cardiac surgery with CPB are related to sepsis. Methods and analysis This study is a prospective observational case–control study to analyse the variation in the intestinal microflora and metabolites in patients undergoing cardiac surgery with CPB and observe the outcomes of patients with routine clinical interventions. The control group will include healthy people without intestinal illness. Faeces and blood samples will be acquired one day before cardiac surgery and within 24-72 hours after cardiac surgery and used for genomics and metabolomics analysis. Demographic data describing age, sex, main diagnosis, and past medical history and data related to the CPB time and application of antibiotics are available. Sequential (sepsis-related) organ failure assessment, infection-related laboratory items, infection site and pathogenic microorganisms, and nutrition and gastrointestinal function assessment are additionally recorded. Group analysis of data will be conducted according to the outcomes (sepsis vs. non-sepsis and survivors vs. non-survivors). Ethics and dissemination This protocol has been ethically approved by the Ethics Committee of Peking Union Medical College (ID: ZS-1612). Informed consent will be obtained before subject enrolment, and data will be stored in a secured database. The results will be submitted to international peer-reviewed journals and presented at international conferences. Trial registration number NCT04032938